The role of mass spectrometry in the characterization of biologic protein products. (4th May 2018) - Rathore, Deepali; Faustino, Anneliese; Schiel, John; Pang, Eric; Boyne, Michael; Rogstad, Sarah
ABSTRACT: Introduction : Mass spectrometry (MS) is widely used in the characterization of biomolecules including peptide and protein therapeutics. These biotechnology products have seen rapid growth over the past few decades and continue to dominate the global pharmaceutical market. Advances in MS instrumentation and techniques have enhanced protein characterization capabilities and supported an increased development of biopharmaceutical products. Areas covered : This review describes recent developments in MS-based biotherapeutic analysis including sequence determination, post-translational modifications (PTMs) and higher order structure (HOS) analysis along with improvements in ionization and dissociation methods. An outlook of emerging applications of MS in the lifecycle of product development such as comparability, biosimilarity and quality control practices is also presented. Expert commentary : MS-based methods have established their utility in the analysis of new biotechnology products and their lifecycle appropriate implementation. In the future, MS will likely continue to grow as one of the leading protein identification and characterization techniques in the biopharmaceutical industry landscape.